1992
DOI: 10.1200/jco.1992.10.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Curability of solitary bone plasmacytoma.

Abstract: In patients with an SBP, the disappearance of myeloma protein with involved-field radiotherapy predicted long-term disease-free survival and possible cure. Nonsecretory disease and persistent myeloma protein after treatment were adverse prognostic factors for which adjuvant therapy with interferon alfa should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 12 publications
0
48
1
1
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From Figure 1B). In contrast to previous studies, [3][4][5][6][7][8][9][10]15 age, sex, vertebral location, or the presence of an M protein at diagnosis or its persistence at 1 year post-irradiation did not predict progression. The value of OMD and ULC were retained in multivariate analysis (P 5 .041 and .009, respectively; Table 1).…”
Section: ) (B)contrasting
confidence: 99%
See 3 more Smart Citations
“…on May 12, 2018. by guest www.bloodjournal.org From Figure 1B). In contrast to previous studies, [3][4][5][6][7][8][9][10]15 age, sex, vertebral location, or the presence of an M protein at diagnosis or its persistence at 1 year post-irradiation did not predict progression. The value of OMD and ULC were retained in multivariate analysis (P 5 .041 and .009, respectively; Table 1).…”
Section: ) (B)contrasting
confidence: 99%
“…The median TTP in this cohort was 49 months (18 months in those who progressed), and this along with the overall proportion of patients progressing is broadly comparable with previous series. [3][4][5][6][7][8][9][10] Progression was documented in 72% (26/34) of patients with OMD compared with 12.5% (2/16) without, and the median TTP was 26 months vs not reached (NR) (P 5 .003; Figure 1A). In a similar analysis, Warsame et al have demonstrated that the presence of clonal plasma cells (as determined by trephine biopsy immunohistochemistry), but below the 10% threshold for the diagnosis of myeloma, was associated with progression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The published data on solitary plasmacytoma of bone suggests a disease-free survival of over 40% at 5 years and median overall survival of over 10 years for similar lesions outside the setting of POEMS syndrome. 16 Significantly, however, the persistence of a relatively small tumour mass in these cases is generally not associated with substantial morbidity. Experience with systemic amyloidosis demonstrates that application of PBSCT may be associated with increased morbidity and mortality in the setting of pre-existing multisystem pathology.…”
Section: Discussionmentioning
confidence: 98%